Preparation of Noodles with High Mung Bean Content and Selection of Suitable Mung Bean Cultivars for Processing - LI Ruo-ning; LIU Xing-hao; LI Chun-hong; HOU Dian-zhi; ZHOU Su-mei (Liang you shipin ke-ji)
Mung bean noodles are traditional multigrain noodles in China, but generally, the addition of green beans is relatively low. Six mung bean cultivars from major production areas were selected to prepare noodles with a high mung bean content of 70%. Then, we screened suitable mung bean raw material varieties for processing based on principal component analysis (PCA). The cooking properties, texture properties, and sensory characteristics of the processed mung bean noodles were analyzed, and relevant data on these properties was collected for analysis. The quality of processed noodles of different mung bean cultivars was evaluated based on PCA. Three types of principal components were extracted from the PCA, and the key indicators of total starch, protein, water absorption, hardness, chewiness and adhesiveness were determined and scored. Finally, we ranked the processing suitability scores for different mung bean varieties and selected the excellent cultivar Weilv 7 to produce high mung bean content noodles.